Developing a framework for attracting tourists to Wudang Mountain, China - Du, Fang (2009)
China has become the fourth most popular destination in the world for foreign travellers, welcoming 29 million visitors from all around the world in 2008 (Euromonitor 2009). In 2008, 37 million Chinese travellers went abroad. Not surprisingly, China is already the largest source of outbound tourism on the Asian continent. Tourism, act as a special role, is becoming an important source of government revenue (Euromonitor 2009). It is believed that it will be interesting to analyse the circumstances of China‟s tourism from a wider point of view. As the market of tourism industry in China has not been completely formed, there are numerous of questions that worth for discussing, therefore, this research is trying to find the answers. Here, Wudang Mountain, a famous resort of China is to choose as the object of analysing characteristics of traditional destinations as well as tourist‟s buying behaviour toward destinations.